Radial growth responses of tulip poplar (Liriodendron tulipifera) to climate in the eastern United States. Issue 10 (22nd October 2020) - LeBlanc, David; Maxwell, Justin; Pederson, Neil; Berland, Adam; Mandra, Tessa
Abstract: Tulip poplar is an important component of the eastern deciduous forest and one of the few diffuse‐porous tree species with indeterminate apical growth in North America for which there are substantial dendroecological data. This dendroecological study evaluated correlations between radial growth of tulip poplar and monthly, seasonal, and annual climate variables and how these correlations varied across time and spatial climate gradients. The strongest and most spatially consistent correlations were with climate variables related to site water balance, especially precipitation. Growth was positively correlated with climate variables related to site water balance during the months of May through July of the year the annual ring forms and during the previous year growing season and autumn. Growth was negatively correlated with prior year growing season maximum temperature, but positively correlated with prior winter minimum temperature. There was some evidence of temporal variation in growth–climate associations between 1900 and 2016, but the climate variables with the strongest associations were consistent across different time periods. Correlations with climate variables related to water stress increased from east to west as precipitation decreased, but there was no spatial trend in correlations with growing season temperature from north to south as temperature increases. Strength of positive correlations with winter temperature increased from north to south. Growth of tulip poplar will likely be adversely affected if drought frequency or severity increases during the twenty‐first century. Increased winter temperature would likely have a positive influence on growth during the subsequent growing season in some parts of the species range. Radial growth of tulip poplar is most affected by climate conditions during a narrow time period early in the growing season, similar to results obtained for multiple oak species and a few other diffuse‐porous species in eastern North America. Simulation modelers might consider the phenology of these correlations to formulate more biologically realistic tree climate response functions.